METODE PENENTUAN AWAL RAMADHAN DAN HARI RAYA MENURUT ULAMA DAYAH ACEH - FAISAL YAHYA YACOB; FAISAL AHMAD SHAH (Universitas Islam Negeri Ar-Raniry, 2016)
Time difference in performing Ramadhan fasting and ‘Id prays colours the situations of Acehnese society nowadays. This difference does not only take place at national level only, such as on Islamic organisations and government, but at Acehnese Dayahreligious experts level as well. The aim this study is to seek information on thoughts of Acehnese Dayah religious experts on methods used in confirming the first day of Ramadhan and ‘Id prays, as well as their opinions on their involvement on the ithbat result conducted by the Indonesian Religious Council. In order to find the answer of the study, interviews were conducted to ten representatives of the biggest Dayahs in Aceh: Al-Aziziyyah, Al-Madinatuddiyyah, and Darussalam Labuhan Haji. The data were analysed with hisab-rukyah hadiths, together with matla’s concept with regards with to Islamic fiqh. The result revealed that Acehnese Dayah religious experts groups employed textual understanding in regards to hisab-rukyah hadiths, and they had different opinion in using hisab in order to object witness. In regard to matla’ concept, however, they approved Abu Makhramah’s Eight-Degree matla’ concept; however, they applied it differently. The majority of them had left the matla’ concept and then change tomatla’wilayahal-hukmwith a reason for general benefits; while other groups were still consistent with the matla’ theory; therefore, they often perform Ramadhan and ‘Id prays on different days from the days the government has announced.